The circular economy rebound effect: Reconceptualizing rebound approaches and mitigation opportunities from an ordonomic perspective - Felix Carl Schultz; Vladislav Valentinov; Robert Jaroslav Reinhardt; Ingo Pies (Journal of Industrial Ecology, 2024)
Recent scholarship has advocated a conceptual investigation of rebound effect theory in the circular economy (CE) context. While the available body of knowledge on a circular economy rebound (CER) is rather scant, this forum article proposes a conceptual view of existing CER approaches. Our analysis reveals that the CER literature has largely bypassed an appreciation of how firm behavior is embedded in and canalized by governance arrangements. This forum article contributes to the literature by reconceptualizing the challenges of mitigating CERs. It proposes to re-focus the CER debate toward: (i) the innovation need of functional collective commitments for CE to address free-rider-problems; (ii) the criticality of effective management of decoupling through innovative circular governance; (iii) the critical reflection of calls for degrowth and “non-optimization” behavior; and (iv) the recognition of optimization behavior and circular governance frameworks as complementary rather than substitute approaches for facilitating CER mitigation.
Keywords: 330; circular economy; circular economy rebound; governance; industrial ecology; ordonomics; rebound effect